Pengembangan Modul Analisis Penggunaan Bahasa Indonesia Mahasiswa Semester VI Program Studi Pendidikan Bahasa dan Sastra Indonesia di STKIP PGRI Lubuklinggau - Dian Ramadan Lazuardi; Sri Murti; Adi Rohman; Sintiyah Permata Sari (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The availability of books related to the Indonesian Language Use Analysis course at the university level is still very few. This is proven by the circulation of books related to the Indonesian Language Usage Analysis course which is not available in the market or books based on e-books on the internet. For this reason, more understanding of the material is needed to be able to master learning outcomes. To achieve this, you can't just rely on the lecturer's explanation. Support is needed from learning resources that can be used for independent study. Moreover, each student has different speed and grasping power, however, teaching materials that can be used independently by students are not yet available. In order to achieve the ultimate goal of this course, teaching materials are needed that are in accordance with the needs of students of the Indonesian Language and Literature Education Study Program STKIP PGRI Lubuklinggau. The required teaching materials are expected based on the linguistic symptoms found in the research. The results of the validity test conducted on three experts showed that the Indonesian Language Usage Analysis module was valid with the hallmark of the module being a module that was developed with the presentation of interactions (stimulus and response). The results of the practicality test based on the prototype test which includes one to one evaluation, small group evaluation and large group evaluation, it can be concluded that the Indonesian Language Usage Analysis module is effectively used in the lecture process. At the formative test stage, it can be concluded that students can understand the material well after using the Indonesian Language Usage Analysis module.